The Effect of the Interaction between Abnormal Body Mass Index and Hypertension on the Risk of Type 2 Diabetes. (16th January 2023) - Hu, Conghui; Su, Yinxia; Hu, Xiaoyuan; Luo, Kun; Abudireyimu, Alimire; Li, Yuanyuan; Yao, Hua
Abstract : Objective . Many patients with type 2 diabetes have an abnormal body mass index (BMI) and hypertension together, but few studies on the interaction of the two on the risk of T2DM are reported. We aim to explore the effect of the interaction between abnormal BMI and hypertension on the risk of type 2 diabetes mellitus (T2DM) in Uyghur residents. Methods and Results . Based on the physical examination data of 27, 4819 Uygur residents in Moyu County, a logistic regression model was used to analyze the correlation between BMI abnormality, hypertension, and T2DM disease, and then, the effect of their interaction on the risk of T2DM was evaluated by an additive model and a multiplicative model. The results showed that the detectable rate of T2DM was 5.58%, the proportion of abnormal BMI was 59.49%, and the proportion of hypertension was 25.14%. The risk of T2DM in people with an abnormal BMI and hypertension was higher than that in people with a normal weight and without hypertension, and the difference was statistically significant P < 0.05 . The additive model showed that after adjusting for confounding factors such as gender, age, family history of diabetes, abdominal obesity, and alcohol consumption, abnormal BMI and hypertension had a synergistic effect on the risk of T2DM and the evaluation indicators RERI, AP, and S were 0.90 (0.32∼1.49), 0.20 (0.11∼0.30), and 1.36 (1.17∼1.57), respectively. But there was no multiplicative interaction between the two (OR = 0.97, (95% CI: 0.89∼1.06). 3). Conclusion . The interaction between abnormal BMI and hypertension can increase the risk of T2DM, and improving BMI and controlling blood pressure within the normal range can effectively reduce the risk of T2DM.